MANAGEMENT DEVELOPMENT AND INDIVIDUAL LEARNING - D. Wahyu Ariani (Akutansi Bisnis & Manajemen ( ABM ), 2002)
Management Development (MD) is the interaction between individu and organization. This is a management and controlling process of management learning in organization with emphasis on strategic or long term activities, so it must be known impact of individual learning behavior and learning opportunity on individual performance. This article has identified four types of management development, Administrative MD, Derived MD, Leading MD, and Partner MD. The central challenge of management development is to control and manage the learning process of managers, focused on individual development and career success and/ or reaching orgnizational goals.